An approach to foster eco-design in 'traditional' companies without eco-knowledge. (2016) - Germani, Michele; Mandolini, Marco; Marconi, Marco; Mengarelli, Marco; Mengoni, Maura; Rossi, Marta
The adoption of an eco-design approach is a key challenge for the total quality environmental management (TQEM). Recently, several eco-design methodologies have been presented, but none can be easily integrated in the traditional design process of manufacturing companies. The research presented in this paper aims to define a methodology, called G.EN.ESI, to help designers (especially those ones without a specific know-how on eco-design), during the development of sustainable products. In order to aid designers in the assessment of the environmental and cost impacts of a product, also a set of software tools have been defined. Using such a platform, the designer is supported by a robust workbench to perform all the analyses required to evaluate the product eco-sustainability for each phase of the product lifecycle. This software platform is essential for companies which want to implement the G.EN.ESI methodology without upsetting their own consolidated modus operandi and the internal organisation.